Pemberdayaan UMKM Desa Gongsol Melalui Digitalisasi Pemasaran - M.Naufal Afif; Qaulan Raniyah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
KKN Mandiri in Gongsol Village, Merdeka District, Karo Regency, aims to empower the community through the digitalization of MSME marketing. The implemented programs include entrepreneurship socialization, savings education, and the introduction of social media as a marketing tool. Using observation and documentation methods, students identified local potential and designed programs tailored to the community's needs. This activity successfully increased community participation and had a positive impact on their well-being and quality of life. Despite facing challenges such as low participation and weather factors, this KKN successfully strengthened MSME potential and contributed sustainably to the development of Gongsol Village